Social Structure Analysis in Management of South Sumatra Inland Waters - Putri, Fevi Rahma Dwi; Satria, Arif; Kinseng, Rilus A.; Taryono, Taryono (Faculty of Fisheries and Marine Universitas Airlangga, 2024)
Abstract The social structure of inland fisheries communities tends to place powerful elites in important positions, while local fishermen are subordinate actors. Patronage is a form of social relationship that describes the unequal social structure between these actors. This research aimed to analyze social structure in the inland waters of South Sumatra in the practice of the Lebak Lebung and River Auction (L3S) in OKI District. To achieve this goal, a constructivist paradigm with qualitative research methods was employed, and the sample comprised 39 informants selected as subjects. The data analysis was conducted in three distinct stages, namely data reduction, presentation, and drawing conclusions. The results showed that the regulation of open access for all parties in the local government regime after 1982 created an institutionalized social relations structure where the government, investors, traders, middlemen, and non-fishing actors dominated compared to the fishermen. The participants in this social landscape strived to accumulate capital to enhance their competitiveness within the L3S domain. A patronage system was implemented with middlemen assuming the role of patron and the fishermen acting as their clients. The current institutional social structure has created an unfair distribution of resource benefits for fishing workers. The novelty theories were found in the working relations of the inland waters community of South Sumatra, namely stratified distribution of rights, dual status, multi-stage patronage, and the positive function of patronage for chief fisherman. Further research should be conducted to research policy revitalization and develop strategic inland water management models. Highlight Research The author mentioned 3 highlights from their results research: Auction system in inland waters in South Sumatra presents an unfair distribution for fishermen. Structure of the working relationship formed is an asymmetric patron-client relationship but with novel theories such as the stratified distribution of rights model, dual status, multi-stage patronage, and the positive function of patronage. An imbalance in local access to auction objects due to their weak ability to accumulate capital.